Comparative Analysis of OCR Methods Integrated with Fuzzy Matching for Food Ingredient Detection in Japanese Packaged Products - Muhammad Zaky Rahmatsyah; Anik Nur Handayani; Jevri Tri Ardiansah (yocto brain, 2025)
Advances in digital technology offer a solution to the challenges faced by foreign consumers in understanding ingredient information on Japanese food packaging, especially due to the use of Kanji, Hiragana, and Katakana characters. This study develops and reveals an allergen detection method based on Optical Character Recognition (OCR) and fuzzy match applied to Japanese food packaging. Three OCR methods—Google Vision OCR, PaddleOCR, and Tesseract OCR—were compared and evaluated using Precision, Recall, F1-Score, and Confusion Matrix metrics.The study began with the collection of food product images from bold sources, followed by text extraction using the three OCR methods. The extracted text was then cleaned and normalized before being matched with ground truth data using fuzzy match. Testing was conducted on 10 product image samples with varying quality and lighting conditions. The results showed that Google Vision OCR outperformed the others, achieving an average F1 score of 1.00, followed by PaddleOCR (0.75), and Tesseract OCR (0.30). Google Vision was the most consistent in detecting allergens such as 乳 (milk), 小麦 (wheat), and 卵 (egg). These findings suggest that the integration of OCR and fuzzy matching is effective in detecting allergens, even in the presence of textual variations and recognition errors. This study contributes to the development of automated food recommendation systems for foreign consumers, especially those who have food preferences due to allergies, religious beliefs, or personal preferences.